2022
DOI: 10.3389/fpsyt.2021.818910
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress Disorder Symptoms and Its Predictors Among Healthcare Workers Following COVID-19 Pandemic in Southern Ethiopia: A Cross-Sectional Study

Abstract: Background: COVID-19 causes immense psychological pressure on communities in addition to physical misery. There is currently a scarcity of data on the psychological impact of the COVID-19 epidemic on Ethiopian healthcare workers (HCWs). Therefore, this study was aimed to assess the post-traumatic stress disorder (PTSD) symptoms and its predictors following COVID-19 pandemic among healthcare workers (HCWs) in southern Ethiopia.Methods: A hospital based cross-sectional study design was used among 387 randomly se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(30 citation statements)
references
References 56 publications
(95 reference statements)
0
29
0
Order By: Relevance
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
“…209 articles continued to the full text screening stage, of which 119 studies were selected for inclusion in our meta-analysis with a total of 117,143 participants ( Table 1A ). All 119 studies were cross-sectional observational studies ( Agberotimi et al., 2020 ; Alah et al., 2021 ; Ali et al., 2020 , 2022 , 2021 ; Alonso et al., 2021 ; Alshehri and Alghamdi, 2021 ; Asnakew et al., 2021 ; Ayalew et al., 2022 ; Azoulay et al., 2021 ; Bassi et al., 2021 ; Benzakour et al., 2022 ; Bizri et al., 2022 ; Bonzini et al., 2022 ; Bulut et al., 2021 ; Caillet et al., 2020 ; Caliandro et al., 2022 ; Carmassi et al., 2022 , 2021a , 2021b ; Chang et al., 2022 ; Chan et al., 2021 ; Chatzittofis et al., 2021 ; Chaudhary et al., 2021 ; B. Chen et al., 2022 ; Cheng et al., 2020 ; Chen et al., 2021 ; Chew et al., 2020 ; Chowdhury et al., 2021 ; Civantos et al., 2020a , 2020b ; Cortés-Álvarez and Vuelvas-Olmos, 2020 ; Costantini et al., 2022 ; Crowe et al., 2022 ; Demartini et al., 2020 ; Dobson et al., 2021 ; Dykes et al., 2022 ; Ergai et al., 2022 ; Essadek et al., 2022 ; Fattori et al., 2021 ; Geng et al., 2021 ; Gilleen et al., 2021 ; Gorini et al., 2020 ; Guo et al., 2021 ; Hajure et al., 2021 ; Hasanvandi et al., 2022 ; Honarmand et al., 2022 ; Hong et al., 2021 ; Huarcaya-Victoria et al., 2022 ; …”
Section: Resultsmentioning
confidence: 99%
“…The qualitative study had fifty respondents [ 35 ], while the most significant number of participants, 420 was recorded in one of the quantitative studies from Ethiopia [ 37 ]. The questionnaire response rates varied between 90%-100%, with most studies dominated by male respondents at 51.9%-69.2% [ 38 ]. Nurses were the commonest study population, followed by doctors, pharmacists, and laboratory technicians, and no study involved non-HCWs of facilities.…”
Section: Resultsmentioning
confidence: 99%
“…Cross-sectional study design minimized selection biases, but many used structured questionnaires, including online self-administered questionnaires, which increased bias due to social desirability. It was not clear how confounding variables were controlled in five papers reviewed [ 38 40 , 43 , 45 ] leading to excessive and perhaps inappropriate determination of associations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While numerous studies have measured and reported that mental health among HCW was poor during the COVID-19 pandemic, [8][9][10][11][12][13] many of these studies did not use validated measures of mental health, used mental health measures that were inappropriate for the culture or language, or used survey distribution and/or completion methods that may have exacerbated adverse mental health symptoms via causing undue stress on the respondent. 14 Nonetheless, the majority of studies have reported poor mental health among HCW during COVID-19.…”
Section: Introductionmentioning
confidence: 99%